CComposite Thrips, Microcephalothrips abdominalis (Crawford, 1910) (Insecta: Thysanoptera: Thripidae)Thripidae) - Rafis A. Khan; Dakshina R. Seal (EDIS)
Microcephalothrips abdominalis (Crawford 1910) (Figure 1) belongs to the order Thysanoptera and the family Thripidae with members commonly known as thrips. Thrips are small, slender-bodied insects with fringed wings, inhabiting diverse ecological niches. Thrips are often cryptic in nature. Microcephalothrips abdominalis prefers to feed on plants in the composite family and therefore is commonly known as composite thrips. Flowers of this family are generally composed of a disk with a ray of petals extending at the rim of the disk. Some flower heads are composed only of a disk or a ray and could be in clusters in some species. https://edis.ifas.ufl.edu/in1232